Sistem Informasi Berbasis Web Untuk Pelaporan Kriminalitas Dan Monitoring Kinerja Pada Seluruh Polsek Di Wilayah Kabupaten Madiun - Pertiwi, Ruly Anggraeni Ega; Aminah, Siti; Tirtana, Arif; Kartikasari, Meivi (LPPM STIKI MALANG, 2022)
In the Madiun, the recording process (incident reporting) carried out by members of the Sector Police still uses printed type and is sent in the form of an official letter. In the police supervision section, the police in this area are still manual, namely recapitulating and printing activities to be reported to the police chief. The purpose of this research is to create a website-based information system that will feature the process of reporting criminal & non-criminal events as well as performance features for police officers who function as supervision and monitoring of police performance. The development method used in this research is a waterfall with the stages of gathering requirements, the design process, implementation, integration or testing and the last is operation. In testing the system, the author uses the Blackbox Testing method in which the functionality of this system will be tested whether it is as expected or not. Based on these tests the authors can draw the conclusion that with this system it can make it easier for police members in the process of reporting criminal and non-criminal events around them and make it easier for the police chief in the process of monitoring or monitoring the performance of his members.